(untitled) (Forum Penelitian Agro Ekonomi, 2016)
English Based on typical agro-ecology and socio-economy conditions, Indonesian agriculture needs agricultural tools and machinery support with certain characteristics. The government has provided agricultural tools and machinery, especially in the last three years, although its success is limited. This paper is a scientific review discussing needs of agricultural tools and machinery for agricultural development, its implementation, and efforts to achieve effectiveness. Materials are compiled from various sources, both documentation of development planning, program reports, as well as the results of critical evaluation and analysis of various research results. The results show that development of agricultural tools and machinery in Indonesia requires a good mapping with respect to the needs and availability, as well as institutional efforts to increase its effectiveness. Use of agricultural tools and machinery can reduce farming costs and provide benefits for farmers and it contributes to food self-sufficiency. Agriculture mechanization has a good prospect if it is preceded by a mapping of needs and availability as well as an adequate institutional environment. Consequently, farm costs become lower and farming efficiency will improve. Indonesian Dengan kondisi agroekologis dan sosial ekonomi yang khas, pertanian Indonesia membutuhkan dukungan penggunaan alat dan mesin pertanian (Alsintan) dengan karakter tertentu. Pemerintah telah lama mengembangkan Alsintan, terutama tiga tahun terakhir, meskipun keberhasilannya masih terbatas. Tulisan ini merupakan review ilmiah (scientific review) yang membahas kebutuhan Alsintan untuk pembangunan pertanian, pelaksanaannya, serta upaya mencapai efektivitas penggunaannya secara optimal. Bahan disusun dari berbagai sumber baik dokumentasi perencanaan pembangunan, laporan program, maupun hasil evaluasi dan analisis kritis dari berbagai hasil penelitian. Hasil analisis menunjukkan bahwa perkembangan Alsintan di Indonesia membutuhkan pemetaan yang baik berkenaan dengan kebutuhan dan ketersediaannya, serta upaya kelembagaan untuk peningkatan efektivitasnya. Penggunaan Alsintan mampu menekan biaya usaha tani dan memberikan keuntungan bagi petani, sehingga mampu berkontribusi pada pencapaian swasembada pangan. Mekanisasi Pertanian mempunyai prospek yang baik kalau didahului dengan pemetaan kebutuhan dan ketersediaan serta langkah langkah kelembagaan (enabling institutional environment) yang memadai. Sebagai konsekuensinya biaya usaha tani dapat ditekan dan efisiensi usaha tani dapat diperbaiki.